Isometries between Spaces of Vector-Valued Differentiable Functions - Alireza Ranjbar-Motlagh (Journal of Function Spaces)
This article characterizes the isometries between spaces of all differentiable functions from a compact interval of the real line into a strictly convex Banach space.